A comparative study on the isolation of B. pseudomallei from soil in endemic areas in Pahang, Malaysia, and the corresponding seropositivity of the inhabitants - Aniza binti Pakeer Oothuman (Kulliyyah of Medicine, International Islamic University Malaysia, 2012)
Melioidosis is caused by a Gram negative saphrophyte Burkholderia pseudomallei and is endemic in Southeast Asia and northern Australia. In Pahang , Malaysia, an increase in reported culture-positive cases has been observed, with many cases presenting with septicaemia carrying a high case fatality rate. This study attempts to determine the rate of isolation of B. pseudomallei in different types of soil, comparing agricultural and non-agricultural soil types. Microbial-specific IgG seropositivity rates of residents and workers from the same areas were also determined for evidence of possible correlation. 350 soil samples were taken from agricultural sites (paddy plantations and oil palm plantations) and non-agricultural sites (Lubuk Yu recreational waterfall park and a construction site). 216 blood samples were taken with informed consent from paddy plantation farmers and residents, oil palm plantation workers and residents, construction site workers and Kampung Sentul (within 5 km of Lubuk Yu) residents. Majority of respondents were male (85.2 %) and labourers (62 %). Paddy farmers and residents had the highest IgG seropositive rate (75 %), followed by oil palm plantation labourers (65 %). Diabetic respondents had 92 % seropositivity. The rate of isolation of B. pseudomallei from soil was 13 % for the paddy plantations, 7 % for oil palm plantations , and 5 % for construction sites. Soil isolation rates were significantly higher in the agricultural areas (p<0.01). Seropositivity rates were also significantly higher in workers and residents of agricultural areas (p<0.01). Statistically significant risk factors for exposure and infection with B. pseudomallei, as signified by IgG seropositivity, were occupation (p<0.05), residential area (p<0.01) and diabetic status (p <0.01). There is a higher B. pseudomallei isolation rate in paddy soil (13 %), coinciding with highest seropositivity rate (75 %), followed by oil palm soil (7%) with seropositivity of 65 %. It is postulated that the higher seropositivity rates in residents and workers of agricultural areas is due to increased exposure to B. pseudomallei by means of agricultural activities.